Genres, styles and discourse communities in global communicative competition: The case of the Franco–American 'AIDS War' (1983–1987). (February 2014) - Helal, Fethi
This article compares the rhetorical strategies employed by American and French scientists in the research article introductions published by both research teams during the so-called 'AIDS War' (1983–1987). The controversy concerned priority rights for the discovery of the AIDS virus. Using Swales's (1990) CARS model as a comparative template, the results indicated that while the Americans proceeded with a deductive, bold and highly elaborated pattern of rhetorical presentation, the French opted for an inductive, more nuanced and unelaborated rhetoric which prioritized the communication of scientific content at the expense of the writers' attitude and personal perspective. The observed variations can be accounted for on the basis of perceptions of what constitutes appropriate academic style during the debate, audience design, power relationships and the sociopolitics of knowledge production in American and French scientific cultures. The article concludes by exploring the implications of these results for the use of English in the resolution of global research problems across the intercultural continuum.